2017
DOI: 10.1088/1361-6587/aa7777
|View full text |Cite
|
Sign up to set email alerts
|

Study of near SOL decay lengths in ASDEX Upgrade under attached and detached divertor conditions

Abstract: A database with attached, partially detached and completely detached divertors has been constructed of ASDEX Upgrade discharges in both H-mode and L-mode plasmas with Thomson Scattering data suitable for the analysis of the upstream SOL electron profiles. By comparing upstream temperature decay width, , , with the scaling of the SOL power decay width, ∥ , based on the downstream IR measurements, it is found that a simple relation based on classical electron conduction can relate , and ∥ well. The combined data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 28 publications
9
33
0
Order By: Relevance
“…These discharges with higher 𝑞 are the same ones mentioned above which will be discussed more in the next section. As observed in the previous study of SOL temperature profile [8], 𝜆 , has a strong 𝑞 dependence, 𝜆 , ∝ 𝑞 for both H-mode and L-mode plasmas. As can be seen from figure 4(a) and (b), 𝜆 , also has a strong 𝑞 dependence, 𝜆 , ∝ 𝑞 , for H-mode plasma.…”
Section: General Observation and Dependences On Global Parameterssupporting
confidence: 81%
See 1 more Smart Citation
“…These discharges with higher 𝑞 are the same ones mentioned above which will be discussed more in the next section. As observed in the previous study of SOL temperature profile [8], 𝜆 , has a strong 𝑞 dependence, 𝜆 , ∝ 𝑞 for both H-mode and L-mode plasmas. As can be seen from figure 4(a) and (b), 𝜆 , also has a strong 𝑞 dependence, 𝜆 , ∝ 𝑞 , for H-mode plasma.…”
Section: General Observation and Dependences On Global Parameterssupporting
confidence: 81%
“…Since the 2014 AUG campaign, significant improvements of the TS system have enabled good measurements of the SOL temperature and density profiles [3]. The Type І ELMy H-mode discharges under attached divertor condition (36 in total) and L-mode attached discharges (27 in total) used in the present dataset are the same discharges as those used in Ref [8]. In H-mode plasma, during ELMs the thermocurrents measured in the divertor are strongly increased, which indicates the onset of an ELM.…”
Section: Experimental Methods and Databasementioning
confidence: 99%
“…The corresponding e-folding lengths are taken from TS data. According to recent L-mode measurements[41], this means λ Te 12 and 20 mm for the low and high collisionality cases, respectively. As can be div > 3 T e,fil /T e,back…”
mentioning
confidence: 90%
“…While so far we have investigated the pedestal stability utilising the common assumption of T e,sep = 100 eV (widely used in the literature [37,38,39,40,41,42,43]) for both H and D cases, we now assess from a qualitative point of view the effect of a potentially higher T e,sep in H on pedestal stability as suggested by the interpretative EDGE2D-EIRENE simulations presented in section 4. The simulations indicated that due to the high power and low density in the H pulse, the divertor may be in sheath limited regime when the T e,sep ∼ P 2/7 scaling breaks down and T e,sep could be much higher than 100 eV.…”
Section: Linear Mhd Pedestal Stabilitymentioning
confidence: 99%